THE EFFECT OF VESSEL SEAWORTHINESS AND CREW’S COMPETENCE ON MARINE SAFETY - Albert Wiweko; Muhamad Thamrin; Dedeng Wahyu Edi (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2015)
The objective is to study the seaworthiness and crew’s competence with marine safety in PT Pulau laut year 2015. This research is quantitative research with correlation and regression methods are applied as data analysis technique to determine the relationship between each variables. The primary data were obtained from questioner which distributed to 73 ship’s crew of PT Pulau Laut using population sampling technique.The result of  this research shows that there is a positive and significant relationship between seaworthiness ship and crew competence with the safety of sea transport.  H3 research hypothesis is accepted where F count> F table or 86.179> 3.128 and the significance probability of 0.000 <0.05 . The R square value is 0,711 or 71,1%. It shows that the contributions of seaworthiness ship and crew competence to marine safety  are 71,1%  and  28,9%are influenced by other factors.